IMPLEMENTASI PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS PROYEKTOR DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI KELAS VI SDIT DARUSSAKINAH BATAM - Palapa, Rieva Arvani; Mariyam; Haya Hamidah; Enik Nurfaizah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The School Environment Introduction (PLP) activity aims to provide real-world experience for students of the Faculty of Tarbiyah and Teacher Training at the Hidayatullah Islamic Institute of Batam in understanding the learning process in schools. One of the aspects observed is the use of technology-based learning media, such as projectors, to support teaching and learning activities. This activity was carried out in Grade VI at SDIT Darussakinah Batam, consisting of 32 students, with a focus on the implementation of projector use in the learning process. The method used was a descriptive qualitative approach, with data collection techniques through observation, interviews, and documentation during the activity. The data obtained were then analyzed using the flow model technique, which includes data reduction to select relevant information. PLP students were directly involved in using the projector media and observing student responses throughout the learning process. The observation results showed that the use of learning media such as projectors can increase student attention and engagement. Learning materials presented in visual form made it easier for students to understand the lessons and created a more interactive learning atmosphere. However, in its implementation, there were still obstacles such as time constraints and a dependence on technological devices that require fast and adequate internet. Overall, the use of projector-based learning media in the teaching and learning process provides a positive contribution to improving learning quality and serves as a valuable experience for students in understanding school teaching practices.